She jiao wang zhan de shu ju wa jue yu fen xi : (yuan shu di san ban) = Mining the social web : data mining Facebook, Twitter, LinkedIn, Instagram, Github, and more - Russell, Matthew A. (Computer scientist); Klassen, Mikhail (O'Reilly jing pin tu shu xi lie., 2021)
Detailed summary in vernacular field.